We have to find the inverse function of f(x) = sqrt(x - 4) + 3.

Let y = f(x)

y = sqrt(x - 4) + 3

=> y - 3 = sqrt(x - 4)

square both the sides

=> (y - 3)^2 = (x - 4)

=> (y - 3)^2...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find the inverse function of f(x) = sqrt(x - 4) + 3.

Let y = f(x)

y = sqrt(x - 4) + 3

=> y - 3 = sqrt(x - 4)

square both the sides

=> (y - 3)^2 = (x - 4)

=> (y - 3)^2 + 4 = x

interchange x and y

=> y = (x - 3)^2 + 4

**The inverse function of f(x) = sqrt(x - 4) + 3 is f(x) = (x - 3)^2 + 4.**